Analysis of the Mismatch of School Education Infrastructure in Supporting Learning Innovation - Fikri Hamdi Siregar; Inom Nasution (Al-Qalam Institue, 2026)
This study aims to analyze the mismatch of educational infrastructure in supporting learning innovation, focusing on infrastructure suitability, principal management, causal factors, and its impact on learning effectiveness. The research employs a qualitative approach with a phenomenological method. Data were collected through semi-structured interviews, observations, and documentation, involving school leaders, teachers, and students. Data analysis followed the Miles and Huberman model, including data reduction, data display, and conclusion drawing, with triangulation to ensure validity. The results indicate that educational infrastructure is generally available but insufficient to optimally support learning innovation. Key constraints include limited technology-based learning media, inadequate classroom conditions, and unstable internet access. Budget limitations, rapid technological changes, and outdated facilities are the main factors contributing to the mismatch. These conditions hinder the implementation of innovative learning, leading teachers to rely on conventional methods and reducing student engagement. This study implies that improving educational infrastructure through adaptive management strategies and stronger policy support is essential to enhance the effectiveness and quality of innovative learning.